Peningkatan Kualitas Pelayanan Pemerintah Desa Balaroa Pewunu - Triachyar Triachyar; Mohammad Zeylo Auriza; Harnida Wahyuni Adda (Jurnal Publikasi Sistem Informasi dan Manajemen Bisnis, 2023)
Balaroa Pewunu Village is one of the villages located in West Dolo Sub-district, Sigi Regency, Central Sulawesi Province. The new village separated itself from the main village of Pewunu in 2012, the establishment of the village was stipulated on November 20, 2012 through Sigi Regency Regional Regulation Number 41 of 2012 concerning the Expansion of Balaroa Pewunu Village. As a village that has not been established for too long, it certainly needs to implement good service quality. The quality of service in Balaroa Pewunu Village is the focus of community service activities. However, the Balaroa Pewunu Village government in terms of administrative services still needs to be improved. This article was prepared to find out about the implementation of improving the quality of service of the Balaroa Pewunu Village Government. The implementation method used is a descriptive qualitative method. Data collection techniques are observation, interviews and documentation. The results achieved from the implementation of community service activities are that the Balaroa Pewunu Village Government has begun to implement related to Improving Service Quality, and since the transition to the new government period. Improvement after improvement, development after development and services that have been implemented have begun to appear, even now Balaroa Pewunu Village has become a model village for neighboring villages.